2019
DOI: 10.1177/0025802419847580
|View full text |Cite
|
Sign up to set email alerts
|

Different predictive and accuracy models for sex and stature estimation from second- and fourth-digit lengths in the Kinnaur population of Himachal Pradesh, North India: Medico-legal and forensic implications

Abstract: Forensic anthropologists are not only active in courtroom testimonies but also contribute to disaster victim identification. The timely recovery and identification of victims in any disaster is crucial, and anthropologists play a vital role in this process. In mass disasters such as airplane crashes, tsunamis, earthquakes or terrorist attacks, fragments of dead bodies are usually brought for identification. Each fragment demands special tactics to fulfil any of the basic attributes of forensic identification s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
3
2
0
Order By: Relevance
“…The hand-related measurement variables of males in Slovakia [18], Turkey [19], Egypt [20], Mauritius [21], North India [7,9,14] and South India [5] have been found to be larger than those of females which were also found in our study. When comparing the parameters with gender difference, Bardale RV et al [1] found correlation coefficient to be higher in females than males while estimating stature from 2DL and 4DL which was also found in our study.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The hand-related measurement variables of males in Slovakia [18], Turkey [19], Egypt [20], Mauritius [21], North India [7,9,14] and South India [5] have been found to be larger than those of females which were also found in our study. When comparing the parameters with gender difference, Bardale RV et al [1] found correlation coefficient to be higher in females than males while estimating stature from 2DL and 4DL which was also found in our study.…”
Section: Discussionsupporting
confidence: 83%
“…Singh B et al Studied the Kinnaur population of Himachal Pradesh and came up with conclusion that 2D provided the best stature estimates [14] which was also found in our study for males. A study on stature estimation from 2DL and 4DL in North Indian population by Krishan et al showed that stature can be estimated with reasonable accuracy from 2DL and 4DL [7] which was also observed in our study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations